2005
DOI: 10.1051/0004-6361:20042568
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of solar off-limb line profiles to electron density stratification and the velocity distribution anisotropy

Abstract: The effect of the electron density stratification on the intensity profiles of the H i Ly-α line and the O vi and Mg x doublets formed in solar coronal holes is investigated. We employ an analytical 2-D model of the large scale coronal magnetic field that provides a good representation of the corona at the minimum of solar activity. We use the mass-flux conservation equation to determine the outflow speed of the solar wind at any location in the solar corona and take into account the integration along the line… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 54 publications
(85 reference statements)
4
10
1
Order By: Relevance
“…For example, Raouafi & Solanki (2004, 2006) simulated the properties of the O VI λλ1032, 1037 lines after first fixing the radial variation of the outflow speed and ion temperature. Figure 5b shows an illustrative "cut" through the data cube at fixed values of u i = 600 km s −1 and w i⊥ = 215 km s −1 at r = 3.09 R ⊙ (similar to the values used by Raouafi & Solanki 2006). In this case, the most probable value of the anisotropy ratio is surprisingly close to 1, as was also assumed by Raouafi & Solanki.…”
Section: Deriving Ion Properties From the Data Cubessupporting
confidence: 64%
“…For example, Raouafi & Solanki (2004, 2006) simulated the properties of the O VI λλ1032, 1037 lines after first fixing the radial variation of the outflow speed and ion temperature. Figure 5b shows an illustrative "cut" through the data cube at fixed values of u i = 600 km s −1 and w i⊥ = 215 km s −1 at r = 3.09 R ⊙ (similar to the values used by Raouafi & Solanki 2006). In this case, the most probable value of the anisotropy ratio is surprisingly close to 1, as was also assumed by Raouafi & Solanki.…”
Section: Deriving Ion Properties From the Data Cubessupporting
confidence: 64%
“…In contrast to many prior analyses of UVCS data, which concluded that there must be both intense preferential heating of the O +5 ions and a strong field-aligned anisotropy, Raouafi and Solanki (2004), Raouafi and Solanki (2006), and Raouafi et al (2007) reported that there may not be a compelling need for O +5 anisotropy depending on the assumptions made about the other plasma properties of the coronal hole (e.g., electron density). However, Cranmer et al (2008) performed a detailed re-analysis of these observations and concluded that there remains strong evidence in favor of both preferential O +5 heating and acceleration and significant O +5 ion anisotropy (in the sense T ⊥i > T i ) above r ≈ 2.1 R ⊙ in coronal holes.…”
Section: Ultraviolet Spectroscopycontrasting
confidence: 64%
“…In addition, we notice that the integration along the line of sight has a significant effect on the spectral line profiles emitted in the solar corona (Raouafi & Solanki 2004, 2006, which could be very important for the resulting polarization of the scattered line. This has to be taken into account for a realistic interpretation of coronal observations.…”
Section: Resultsmentioning
confidence: 97%
“…The calculations are restricted to an emitting elementary volume around the plane of the sky. Integration along the line of sight is outside the scope of the present works, but see Raouafi & Solanki (2004, 2006. In fact, polarization measurements of scattered lines which are optically thin most often concern observations made at the limb.…”
Section: Introductionmentioning
confidence: 95%